(untitled) (Clinics, 2011)
BACKGROUND: Asthma and rhinitis often coexist, which potentially increases the disease severity and can negatively impact a patients' quality of life. However, there are few reports based on data obtained from the International Study of Asthma and Allergies in Childhood examining asthma severity in combination with rhinitisrelated symptoms. OBJECTIVE: To demonstrate whether current rhinitis and current rhinoconjunctivitis are associated with the development of asthma or its increasing severity in Brazilian adolescents. METHODS: The prevalence of current asthma was correlated with the prevalence of current rhinitis and current rhinoconjunctivitis in adolescents (13 to 14 year olds) from 16 Brazilian centers (based on Spearman's rank correlation index). The influence of current rhinitis and current rhinoconjunctivitis on asthma presentation was also evaluated using the chi-squared test and was expressed as odds ratios with 95% confidence intervals (95%CI). RESULTS: A significant positive correlation was observed between the prevalence of current asthma and current rhinitis (rs = 0.82; 95%CI: 0.60-0.93, p< 0.0001) and between the prevalence of current asthma and current rhinoconjunctivitis (rs = 0.75; 95%CI: 0.47-0.89, p < 0.0001). Current rhinitis was associated with a significantly increased risk of current asthma and of more severe asthma. Similar results were observed for current rhinoconjunctivitis. CONCLUSION: In this epidemiologic study of Brazilian adolescents, the presence of current rhinitis and current rhinoconjunctivitis was associated with a high risk of developing asthma and increased asthma severity. The mutual evaluation of rhinitis and asthma is necessary to establish an adequate treatment plan.